Clarifying the construct of compassion: ability to downregulate emotion as a potential mediator between empathic arousal and compassion - Merriman, Leslie A., author; Rickard, Kathryn, advisor; Allen, Chris, committee member; Chavez, Ernest, committee member; Souza, Caridad, committee member (Colorado State University. Libraries, 2017)
The association between empathy and compassion was examined in a sample of Americans aged 35 to 86, using national survey and phone interview data, biological data, and neuropsychological data. Given the postulation that empathy is a necessary, but not sufficient, condition for compassion to emerge, compassion is conceptualized here as an emergent process that is contingent upon empathic arousal. The degree to which an experience of empathic arousal translates into compassion is hypothesized to depend upon an individual's ability to downregulate the emotional response associated with empathic arousal, which is conceptualized as physiological upregulation in response to witnessing another's suffering. If this hypothesis is supported, then the ability to downregulate physiological processes associated with empathic arousal should mediate a positive association between the activation of empathic feelings and engagement with compassionate behavior. While empathic arousal was found to predict compassion, we were unable to infer that downregulation processes mediated the relationship. The results of this study present preliminary findings that may inform future work aiming to clarify the construct of compassion. The results may also provide useful groundwork for future work about "compassion fatigue" and about how the emergence of compassionate action in therapeutic interactions can be cultivated.
Keywords: compassion; empathy; compassion fatigue; Buddhism